Analysis of dynamics for anomalies of the ice cover in the Okhotsk Sea in the period from 1882 to 2015 - Vladimir M. Pishchalnik; Valery A. Romanyuk; Igor G. Minervin; Alevtina S. Batuhtina (Известия ТИНРО, 2016)
The time-series for the ice cover dynamics in the Okhotsk Sea in the period from 1882 to 2015 are reconstructed on the base of shipboard, airborne, and satellite observations and measurements of the air temperature at the coastal meteorological stations. Abnormality of the ice conditions is estimated relative to the “climate norm” determined as the mean seasonal variation for the 1961-1990. Long-term variability of the ice cover is analyzed. Its regime shift with change of trend is revealed in the late 1970s - early 1980s that corresponds to the regime shift of the air temperature variability in the northern hemisphere.